Evaluation of anti-ulcer activity of ethanolic extract of Dactyloctenium aegyptium (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
The ethanolic extract of Dactyloctenium aegyptium was investigated for its anti-ulcer activity against aspirin plus pylorus ligation induced gastric ulcer in rats, HCl -Ethanol induced ulcer in mice and water immersion stress induced ulcer in rats at 300 mg/kg body weight. p. o. A significant (P